2019
DOI: 10.1111/ane.13058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of new-onset and persistent epilepsy in the elderly

Abstract: Epidemiological studies show that the incidence of epilepsy is significantly higher in the elderly than in any other age groups, and the prevalence of epilepsy increases rapidly with age except in the very young population. 1 The high prevalence of epilepsy in the elderly may result from the more frequent epilepsy-associated neurological diseases such as stroke and traumatic brain injury, 2 but the improved survival of previously diagnosed epilepsy patients can affect the high prevalence in the elderly populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The mortality of status epilepticus is known to be highest in the oldest, and it has been shown that new-onset epilepsy has a higher incidence of status epilepticus in the elderly population. 18 Although its incidence has not been investigated in the subgroup of myoclonic status epilepticus, a mortality rate of approximately 50% in has been reported in overall patients with status epilepticus those over 80 years of age. 19 Hence, we also suggest that in presentations of atypical movement disorders in elderly patients, performing EEG may be a vital tool for the proper diagnosis and timely interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality of status epilepticus is known to be highest in the oldest, and it has been shown that new-onset epilepsy has a higher incidence of status epilepticus in the elderly population. 18 Although its incidence has not been investigated in the subgroup of myoclonic status epilepticus, a mortality rate of approximately 50% in has been reported in overall patients with status epilepticus those over 80 years of age. 19 Hence, we also suggest that in presentations of atypical movement disorders in elderly patients, performing EEG may be a vital tool for the proper diagnosis and timely interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality of status epilepticus is known to be highest in the oldest, and it has been shown that new-onset epilepsy has a higher incidence of status epilepticus in the elderly population. 18 Although its incidence has not been investigated in the subgroup of myoclonic status…”
Section: Videomentioning
confidence: 99%